2018
DOI: 10.1002/hyp.13224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of land cover and hydro‐meteorological controls on soil water DOC concentrations in a high‐elevation tropical environment

Abstract: Páramo soils store high amounts of organic carbon. However, the effects of climate change and changes in land cover and use (LC/LU) in this high‐elevation tropical ecosystem may cause a decrease in their carbon storage capacity. Therefore, better understanding of the factors influencing the Páramo soils' carbon storage and export is urgently needed. To fill this knowledge gap, we investigated the differences in dissolved organic carbon (DOC) content in the soil water of four LC/LU types (tussock grass, natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…The authors determined one of the largest DOC export fluxes in a forested tropical catchment (13.79 ± 2.07 g C · m ‐2 · year ‐1 ). Contrary to the latter findings, Pesántez et al () reported that changes in land cover and use are the most important predictor of DOC concentrations in high‐elevation ecosystems of Ecuador, with minimal influence of precipitation conditions. Table shows a summary of DOC export fluxes in a wide range of tropical, temperate, arctic, and large river systems across the globe for comparison purposes.…”
Section: Introductionmentioning
confidence: 88%
“…The authors determined one of the largest DOC export fluxes in a forested tropical catchment (13.79 ± 2.07 g C · m ‐2 · year ‐1 ). Contrary to the latter findings, Pesántez et al () reported that changes in land cover and use are the most important predictor of DOC concentrations in high‐elevation ecosystems of Ecuador, with minimal influence of precipitation conditions. Table shows a summary of DOC export fluxes in a wide range of tropical, temperate, arctic, and large river systems across the globe for comparison purposes.…”
Section: Introductionmentioning
confidence: 88%
“…Below the polypropylene plates, the remaining part of the wicks were placed inside a flexible silicon tube and protected with a 60 cm long and 3/4″ diameter plastic pipe to ensure an unhindered and constant vertical suction of approximately 60 hPa (Windhorst, Kraft, Timbe, Frede, & Breuer, ). Each silicon tube was routed to a centralized collection pipe (Ø = 50 cm) where it was connected to a 1.5‐L glass bottle where collected water was stored until analysis (Pesántez et al, ). The wick samplers were installed at 10, 35, and 65 cm depths at each sampling site.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
“…The study was carried out at a tropical alpine (Páramo) experimental hillslope situated in the headwaters of the Quinuas Ecohydrological Observatory in south Ecuador (2°47′S, 79°13′W) between 3,900 and 4,100 m a.s.l. The hillslope (Figure a) has a steep gradient (42%; similar to the average slope of the Quinuas Observatory; Pesántez, Mosquera, Crespo, Breuer, & Windhorst, ) and is covered by the dominant Páramo vegetation, consisting primarily of tussock grass ( Calamagrostis intermedia ), locally known as “pajonal,” which covers more than 75–80% of conserved Páramo areas (Mosquera, Lazo, Célleri, Wilcox, & Crespo, ). The soils at the study region resulted from the accumulation of volcanic ash deposits during Quaternary activity in combination with the humid and cold local climate conditions (Buytaert et al, ).…”
Section: Experimental Hillslope Descriptionmentioning
confidence: 98%
“…Also, the Ksat of pine plantation soils showed a negative relationship with the herbaceous species richness and its cover. This relationship is due to the fact that plantations with a high Ksat show a high speed of water movement in the soil, causing fast drying [74] and loss of SOM [87], limiting the development of herbaceous plants. Therefore, we can conclude that besides elevation, herbaceous species richness and its cover within plantations depend substantially on the attributes of the plantations as well as on the properties of the soils.…”
Section: Natural Regeneration Influenced By Pine Plantation Attributementioning
confidence: 99%